PERAN DIALEKTIKA DAN METODOLOGI ILMU SEJARAH PADA UPAYA PENGUATAN LITERASI DIGITAL - gilangtrisubekti gilangtrisubekti (Madaris: Jurnal Guru Inovatif, 2021)
The era of disruption, a movement in the industry is no longer linear. It is very fast and tends to ruffle the pattern of the old order, and tends to form a new order pattern. For the record, the industrial revolution has happened four times. First with the invention of the steam engine, the second is electrification, computer invention, and the age of digital revolution. The bad side is this era is the spread of hoax are increasingly out of control and rampant. A firehose of falsehood - the terminology that I used in this article - is a basic term for political science to refer to lies, one of the techniques of agitation and propaganda by means of spreading lies massively, integrated and structured in print/daring media or social media. The goal is to obscure the truth. The historical method, of course along with the methodology of other humanities as well as the scientific sciences, if applied, are able to hone student’s critical thinking in the fight against hoax. Because the key to knowing hoax or true is verification, one of the step in the historical methodology. In this case, this critical thinking indirectly is in the method of science in each subject in the madrasah.